β2-Adrenoceptors activation regulates muscle trophic-related genes following acute resistance exercise in mice - Abdalla-Silva, Ronaldo L.; Zanetti, Gustavo O.; Lautherbach, Natalia; Schavinski, Aline Zanatta; Heck, Lilian C.; Gonçalves, Dawit A. P.; Kettelhut, Isis C.; Navegantes, Luiz C. C.; Silveira, Wilian A. (Frontiers in Physiology, 2024)
Resistance exercise (RE) training and pharmacological stimulation of β2-Adrenoceptors (β2-ARs) alone can promote muscle hypertrophy and prevent muscle atrophy. Although the activation of the sympathetic nervous system (SNS) is a well-established response during RE, the physiological contribution of the endogenous catecholamines and β2-ARs to the RE-induced changes on skeletal muscle protein metabolism remains unclear. This study investigated the effects of the β2-ARs blockade on the acute molecular responses induced by a single bout of RE in rodent skeletal muscles. Male C57BL6/J mice were subjected to a single bout of progressive RE (until exhaustion) on a vertical ladder under β2-AR blockade with ICI 118,551 (ICI; 10 mg.kg-1, i.p.), or vehicle (sterile saline; 0.9%, i.p.), and the gene expression was analyzed in gastrocnemius (GAS) muscles by qPCR. We demonstrated that a single bout of RE acutely increased the circulating levels of stress-associated hormones norepinephrine (NE) and corticosterone (CORT), as well as the muscle phosphorylation levels of AMPK, p38 MAPK and CREB, immediately after the session. The acute increase in the phosphorylation levels of CREB was followed by the up-regulation of CREB-target genes Sik1, Ppargc1a and Nr4a3 (a central regulator of the acute RE response), 3h after the RE session. Conversely, β2-AR blockade reduced significantly the Sik1 and Nr4a3 mRNA levels in muscles of exercised mice. Furthermore, a single bout of RE stimulated the mRNA levels of the atrophic genes Map1lc3b and Gabarapl1 (autophagy-related genes) and Mstn (a well-known negative regulator of muscle growth). Unexpectedly, the gene expression of Igf-1 or Il-6 were not affected by RE, while the atrophic genes Murf1/Trim63 and Atrogin-1/Mafbx32 (ubiquitin-ligases) were increased only in muscles of exercised mice under β2-AR blockade. Interestingly, performing a single bout of RE under β2-AR blockade increased the mRNA levels of Mstn in muscles of exercised mice. These data suggest that β2-ARs stimulation during acute RE stimulates the hypertrophic gene Nr4a3 and prevents the overexpression of atrophic genes such as Mstn, Murf1/Trim63, and Atrogin-1/Mafbx32 in the first hours of postexercise recovery, indicating that he SNS may be physiologically important to muscle adaptations in response to resistance training.